Сlinical Case of Macular Hole Recurrence after Surgical Treatment with Platelet-Rich Plasma - D. V. Cherepov; S. J. Goziev (Oftalʹmologiâ, 2020)
Purpose: presentation of a clinical case of an idiopathic macular hole (IMH) recurrence after its successful closure augmented with platelet-rich plasma (PRP) and the results of repeated surgical treatment.Methods. The patient underwent clinical examination and optical coherence tomography (OCT) of the retina before and after surgical treatment. А 2-stage surgical treatment of the left eye with an interval of 7 days: phacoemulsification (PE) followed by microinvasive vitrectomy with Internal limiting membrane peeling (ILM) and closure with the use of PRP. The patient was discharged with improved visual acuity and closure of the macular hole (MH). After 2 weeks vision deterioration was noted by the patient in the operated eye. Clinical examination revealed macular edema (ME) and recurrence of MH. Topical steroid eye drops were used to no avail, with increase of ME and MH via OCT control. Revision of the vitreal cavity augmented with PRP was performed.Results. In follow-up a complete closure of the MH, resolution of ME and improvement in visual acuity after repeated surgery was confirmed.Conclusions. A case of recurrent MH after primary closure with PRP is described. The case suggests a possibility of clinical improvement after repeated MH closure augmented with PRP. The causes and mechanisms of the recurrence of MH are still not clear. Despite the positive results of surgery subsequent OCT retina examination is necessary.